Combined Self-Nanoemulsifying and Solid Dispersion Systems Showed Enhanced Cinnarizine Release in Hypochlorhydria/Achlorhydria Dissolution Model - Ahmad A. Shahba; Ahmad Y. Tashish; Fars K. Alanazi; Mohsin Kazi (MDPI AG, 2021)
The study aims to design a novel combination of drug-free solid self-nanoemulsifying drug delivery systems (S-SNEDDS) + solid dispersion (SD) to enhance cinnarizine (CN) dissolution at high pH environment caused by hypochlorhydria/achlorhydria. Drug-loaded and drug-free liquid SNEDDS were solidified using Neusilin® US2 at 1:1 and 1:2 ratios. Various CN-SDs were prepared using freeze drying and microwave technologies. The developed SDs were characterized by differential scanning calorimetry (DSC) and X-ray powder diffraction (XRD). In-vitro dissolution studies were conducted to evaluate CN formulations at pH 6.8. Drug-free S-SNEDDSs showed acceptable self-emulsification and powder flow properties. DSC and XRD showed that CN was successfully amorphized into SDs. The combination of drug-free S-SNEDDS + pure CN showed negligible drug dissolution due to poor CN migration into the formed nanoemulsion droplets. CN-SDs and drug-loaded S-SNEDDS showed only 4% and 23% dissolution efficiency (DE) while (drug-free S-SNEDDS + FD-SD) combination showed 880% and 160% enhancement of total drug release compared to uncombined SD and drug-loaded S-SNEDDS, respectively. (Drug-free S-SNEDDS + SD) combination offer a potential approach to overcome the negative impact of hypochlorhydria/achlorhydria on drug absorption by enhancing dissolution at elevated pH environments. In addition, the systems minimize the adverse effect of adsorbent on drug release.